P084 Experiences With The Novel Policy For Managing Conflicts Of Interest Implemented In The 9th Edition Of The American College Of Chest Physicians Antithrombotic Guidelines (At9). (15th August 2013) - Neumann, I; Karl, R; Rajpal, A; Akl, E; Guyatt, G
Abstract : Background: The executive committee of the American College of Chest Physicians 9th edition of the Antithrombotic Guidelines (AT9) developed a novel policy for managing conflicts of interest (COI): methodologists bore primary responsibility for each chapter; there was equal emphasis on intellectual and financial COI; and content experts with COI participated, but the intent was to exclude them from the final decisions on recommendations on which they had conflicts. Objectives: To explore the experiences of the AT9 methodologists and content experts with the COI policy. Methods: A descriptive qualitative study: We conducted two rounds of semi-structured interviews with 15 participants and presented the results to the remaining 4 for verification. Results: Methodologists were more positive about the policy than content experts. Six of 10 content experts expressed a more positive view than prior to participation in the AT9 process. The other 4 content experts remained sceptical, especially regarding the emphasis on intellectual COI. It was not possible to completely exclude conflicted panellists from the final decisions of the recommendations on which they had COI. Discussion: After its implementation, some content experts were more favourable to the policy, but some retained major reservations. The influence of the policy on recommendations may have been more through the leading role of the methodologists than exclusion of conflicted participants in making recommendations. Implications for Guideline Developers/Users: The leading role of methodologists was a positive innovation. However, restrictions to conflicted panellists were difficult to fully implement.